Numerical study on the thermal performance of the shell and tube heat exchanger using twisted tubes and Al2O3 nanoparticles. (January 2023) - Ghazanfari, Valiyollah; Imani, Morteza; Shadman, Mohammad Mahdi; Amini, Younes; Zahakifar, Fazel
Abstract: In the present study, the influence of twisted tubes and Al2 O3 nanofluid on the thermal performance of the shell and tube heat exchanger is numerically studied. It employed computational fluid dynamics (CFD) with different turbulence models (realizable k-ε and realizable k-ε 2nd order). To verify the present solution, the results were compared with the published study in which the first-order realizable k–ε model was nominated as the acceptable method. In this study, mass flow rates ranging from 0.5 kg/s, 1 kg/s, and 2 kg/s were considered to investigate the thermal performance. Furthermore, pure water and the Al2 O3 nanofluid 5%, 10%, 15%, and 20% were used for twisted tubes, and only pure water was employed for smooth tubes heat exchangers with 6 baffles and without baffles. The results demonstrated using twisted tubes instead of smooth tubes, the coefficient of heat transfer increased by about 20%, but the pressure drop increased by about 14%. The results presented that the simultaneous use of 20% nanofluid and twisted tubes (instead of the pure water and smooth tubes with 6 baffles) leads to about an 8% increase in heat transfer coefficient and reduces the pressure drop by about 40%. Therefore, using nanofluids and twisted tubes can increase the thermal performance and reduce the economic costs of the pump compared to the old heat exchangers with various baffles. Highlights: The effect of twisted tubes and Al2O3 nanofluid in shell and tube heat exchanger was investigated using the 3D numerical solution. Various simulations, including smooth and twisted tubes, with and without baffles and using different nanofluid concentrations, were investigated to analyze the heat exchanger. Using the twisted tube instead of the smooth tube increased the heat transfer coefficient by about 25% but increased the pressure drop by 13%. Using 6 baffles in a smooth tube heat exchanger increased the heat transfer coefficient by 110% but increased the pressure drop by 120%. The thermal performance of a twisted tube heat exchanger with 20% nanofluid is similar to a heat exchanger with 6 baffles, while the pressure drop is approximately 40% lower.